Pauli spin blockade in CMOS double quantum dot devices. Issue 3 (21st February 2017) - Kotekar‐Patil, D.; Corna, A.; Maurand, R.; Crippa, A.; Orlov, A.; Barraud, S.; Hutin, L.; Vinet, M.; Jehl, X.; De Franceschi, S.; Sanquer, M.
Abstract: Silicon quantum dots are attractive candidates for the development of scalable, spin‐based qubits. Pauli spin blockade in double quantum dots provides an efficient, temperature independent mechanism for qubit readout. Here, we report on transport experiments in double gate nanowire transistors issued from a complementary metal–oxide–semiconductor (CMOS) process on 300 mm silicon‐on‐insulator wafers. At low temperature the devices behave as two few‐electron quantum dots in series. We observe signatures of Pauli spin blockade with a singlet–triplet splitting ranging from 0.3 to 1.3 meV. Magneto‐transport measurements show that transitions which conserve spin are shown to be magnetic‐field independent up to B = 6 T.